STUDI POTENSI DAN DINAMIKA STOK IKAN LEMURU (Sardinella lemuru) DI SELAT BALI SERTA ALTERNATIF PENANGKAPANNYA - Daduk Setyohadi (Universitas Gadjah Mada, 2009)
The research was conducted at Bali Straits on April to September 2007. The aims of this study were (1) to estimate potential sustainable yield (MSY) and total allowable catch (TAC); (2) to estimate status and potential exploitation; and (3) to make some scenario of the alternatives fisheries management. Catch-effort data time series was taken from Fisheries Statistics Report of Bali. The data analysis was performed by using holistic models as stated by Walter & Hilborn (1976) and Schnut (1977). The result of this research showed that the potential sustainable reserve of oil sardine (Be); MSY and TAC were 208,152.2; 23,447.9 and 18,758.3 ton year-1, respectively. Exploitation rate was equal to 105% yr-1, it means the exploitation status of the oil sardine was over exploited. The scenario of this fisheries management of purse seine should be maintained at 24 unit yr-1, the potential sustainable reserve will reach 207,000 ton in year 2020 and the MSY will be increased twice.